The determination of Acanthamoeba spp. from air ventilation system samples from selected buildings in Kuantan - Md Isa, Muhammad Lokman; Aznan, Anis Amira; Mat Amin, Nakisah; Mat Yusof, Afzan (IIUM Press, 2018)
Objective: The present study is designed to investigate the occurrence of Acanthamoeba in air ventilation and air-conditioning systems in selected buildings in Kuantan. Methods: Acanthamoeba was isolated from dust samples taken from filters of air ventilation systems in selected buildings in Kuantan. The dusts were collected by using sterile cotton swabs, cultured in a xenic culture medium on non-nutrient agar (NNA) plates and incubated at 37º C. The plates were examined daily for any presence of Acanthamoeba cysts up to 7 days of incubation. Results: Based on the results obtained, there were no cysts or trophozoites of Acanthamoeba successfully isolated from all 75 dust samples. After three days of incubation, all culture plates examined show negative findings. Conclusions: The negative findings of this study were probably due to the limitations of the sampling method. It is recommended that future studies use the method proposed by National Institute of Occupational Safety and Health (NIOSH) for indoor air quality monitoring.